Effect of establishment methods and nutrient management on productivity and energetics of rice (Oryza sativa) - POORNIMA, S; SINGH, Y V; SHIVAY, Y S; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was carried out during kharif season of 2017–18 at ICAR-IARI, New Delhi to study the effect of crop establishment methods and nutrient management options on and energetics of rice (Oryza sativa L) (cv. Pusa Basmati 1509). The experiment was laid out in split-plot design with three replications. The treatments comprised two main plots, viz. aerobic rice (AR) and conventional transplanted (CT) rice and three sub-plots, viz. 100 % RDF (120:60:60 kg N: P2O5: K2O); 100 % RDF + biofertilizers (bf) and 125 % RDF. Results showed that plant growth and yield were significantly superior in CT rice than AR. In case of nutrient management, application of 125% RDF gave significantly higher grain (4.76 and 5.17 t/ha) and biological yields (11.77 and 12.55 t/ha) and those were at par with 100% RDF + bf. Likewise, significantly higher energy input (25.19 and 25.15 ×103 MJ/ha), output (158.85 and 168.62×103 MJ /ha) was recorded in CT than AR and net energy obtained was non-significant. Among nutrient management options, significantly higher energy input were consumed in 125% RDF followed by 100% RDF +bf and 100% RDF and the energy output was also higher with 125% RDF and 100 % RDF + bf. Hence, CT rice along with 100% RDF + biofertilizers may be recommended for farmers to get higher productivity, profitability and energy values. But in case of water scarce conditions, aerobic rice can be recommended with 100% RDF+ biofertilizers with slight penalty in grain yield and net returns.